Axial Double-Ball Test Versus the Uniaxial Unconfined Compression Test for Measuring the Compressive Strength of Freshwater and Sea Ice - Kovacs, Austin (1993)
Axial double-ball load tests were made on freshwater ice and first- year and multiyear sea ice. From this simple test method the apparent unconfined compressive strength of the ice was determined. These strength results were compared with those obtained from the complex and costly uniaxial unconfined compression test made on similar ice at a strain rate of 10-3 s-1. The scatter in the test data and the average ice strength obtained from both test methods were similar. The findings indicate that the expedient axial double-ball load test is well suited for determining the unconfined compressive strength of ice, especially in the field where the demanding sample preparation requirements needed for unconfined compression test samples cannot be met. Compressive strength, Ice, Sea ice, Freshwater ice, Ice strength.